The impact of training on employees' performance in an entrepreneurial environment in Serbia: empirical and statistical findings - Zorana Nikitović; Aleksandra Penjišević; Borko Somborac (Anali Ekonomskog fakulteta u Subotici, 2023)
The efforts of organizations to improve their business processes, establish market competitiveness, more efficiently achieve goals, and increase profitability, are mainly done through an attempt to upgrade the performance of employees. Increasing the employees' work performance is directly correlated with the improvement of individual skills, as well as the level of ability to effectively transform new knowledge according to daily work obligations. In this process, synergies should be established between employees, on the one hand, who should be adequately motivated, committed, and focused on the acquisition of new knowledge, and on the other hand, organizations that should provide resources, support, and conditions for effective knowledge transfer from educational process to visible improvement indicators of different employees performance levels. The purpose of this paper is to investigate the impact of training on increasing the individual and organizational performance of employees in entrepreneurial organizations in Serbia. Additionally, the correlation between the two groups of respondents, managers and non-managerial staff, will be tested, to determine more closely whether there is a distinction in relation to the position held by the respondent, for defined issues.